Preventing Foodborne and Non-foodborne Illness: Vibrio parahaemolyticus - Anita C. Wright; Renée M. Goodrich-Schneider; Michael A. Hubbard; Keith R. Schneider (EDIS)
FSHN09-01, a 3-page fact sheet by Anita C. Wright, Renée Goodrich Schneider, Michael A. Hubbard, and Keith R. Schneider, describes this bacterium that occurs naturally in coastal waters throughout the world and is linked to illnesses associated with consumption of raw or improperly cooked seafood — type of illness, who is at risk of infection, how common infections are, how they occur, how to receive and store seafood and shellfish, and methods to prevent infection in high-risk individuals. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2009.